Studi Tentang Komunikasi Bahasa Menurut Jahidz Dan Ibnu Jinni - Azzah Diana Mardhotillah; Afiyatul Maulidiyah; Aulia Rohmah; Muflihah (Jurnal Pendidikan Bahasa Arab, 2025)
The study of language communication according to Jahiz and Ibnu Jinni provides deep insight into classical linguistic thought in the Arabic context. "Al-Jahiz'', an important figure in the history of Arabic linguistics, developed the theory of "nazm'' which emphasized the relationship between pronunciation, meaning, and social context. He argued that the formation of language meaning cannot be separated from its historicity and suggested the existence of a strong relationship between language elements such as pronunciation, signs, writing and contracts.Meanwhile, "Ibn Jinni" defines language as the sounds used by society to convey meaning. He emphasized that language is a social phenomenon that has a function in the context of certain groups. In his work "Al-Khasha'is", Ibn Jinni describes the sound characteristics and social functions of language and distinguishes between terms such as lahjah (dialect) and fushah (standard). He also introduced the “qiyas” method for creating new languages, which demonstrated an analytical approach in understanding the structure and use of language.These two thinkers show that language communication is not just a tool for interaction, but also reflects the social and cultural identity of society. Thus, their study makes a significant contribution to the understanding of modern linguistics and the social relevance of language.